OPINI PUBLIK TERHADAP KEBIJAKAN PENUTUPAN TIK TOK SHOP (STUDI LITERATUR DAN ANALISIS SENTIMEN) - Mirandini, Nabila Ayu; Kuswari, Nurul I.; Revinta, Septian N.; Putri, Yulia S. F. (Peneliti.net, 2024)
The development of technology and information has led to the emergence of various innovations in diverse fields including economic aspects. The utilization of Tik Tok Shop as an online shopping platform has spring up. Apart from the benefits, especially to local MSMEs, the Indonesian government has taken firm steps to shut the platform as stated in Minister of Home Affairs Regulation Number 31 of 2023 (Permendagri Nomor 31 Tahun 2023). The decision reaped pros and cons in society, especially on social media. This research aims to analyze the impact of issuing policies regarding the shutdown of the Tik Tok Shop as well as public responses and opinions towards these policies using literature study methods and sentiment analysis with the Naïve Bayes algorithm. This research found that 771 out of 1005 xeets (previously tweet) containing public opinions had negative sentiment with an accuracy rate of 71%.